Comprehensive evaluation of abattoirs with no Hazard Analysis Critical Control Point plan in Tucumán, Argentina = Evaluación integral de frigoríficos sin un plan de análisis de peligros y puntos críticos de control en Tucumán, Argentina - Pérez Terrazzino, Gabriela; Costa, Magdalena; López Campo, Alejandro; Saade, Carolina; Moreno Mochi, María Paula; Signorini Porchiett, Marcelo Lisandro; Roge, Ariel; Van Der Ploeg, Claudia; Leotta, Gerardo; Jure, María Ángela (Elsevier, 2023)
This work focused on the comprehensive study of two provincial transit abattoirs in Tucumán, Argentina, with no Hazard Analysis Critical Control Point (HACCP) plan. Visits (n = 20) were conducted between 2016 and 2018 during the operational and post-operational processes. Risk was estimated and the bacteriological analysis of carcass and environmental samples was performed. Risk estimation showed the predominance of high risk in both abattoirs. The main deviations from the HACCP plan were: deficient building conditions, deficient workflow, lack of sectorization of changing rooms and bathrooms, lack of implementation of Standardized Sanitary Operational Procedures, and no food safety training of workers. The counts of indicator microorganisms from both abattoirs were not significant. Salmonella spp. was isolated from 7.5% carcass and 7.3% environmental samples. The Salmonella serovars identified were Cerro, Corvallis, Havana and Agona. Shiga toxin (stx) genes were detected in 24.4% carcass and 30.9% environmental samples. The isolates were characterized as Escherichia coli O8:H7/stx1, O116:H49/stx2 and O136:H40/stx2. Based on these results, it would be possible to implement an improvement plan in Tucumán abattoirs together with the local health authorities. Still, the need to work jointly with the sanitary authority in search of a unique sanitary standard for Argentina remains unaddressed.